The Union and Progress Society and its political role in the Ottoman Empire 1889 - 1918 AD - صالح, هيلين; ربيع عثمان,; وسام عياش , (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
The Union and Progress Society had a great impact on the political developments that the Ottoman Empire witnessed in the late nineteenth century and the beginning of the twentieth century, as this society and its members played a decisive role in the coup that took place against Sultan Abdul Hamid II, which led to his removal from the throne in 1908 AD, and the leaders of this society took over the reins of government and authority in the Ottoman Empire, following a policy contrary to what they called for in terms of principles calling for freedom, justice and equality, before they assumed power, as they followed a policy of Purification and attempted to melt all nationalities subject to the Ottoman Empire in the Turkish crucible, which led to many disturbances and revolutions against the Ottoman government led by the unionists. The Ottoman Empire witnessed many political developments under the Union and Progress government, the most prominent of which was the fall of the Libyan state as prey to the Italian occupation, in addition to serious developments in the Armenian issue, as well as the Ottoman Empire's entry into World War I alongside Germany and its loss of this war, which led to the end of the rule of the two unions and their escape outside the Ottoman Empire.